ETIKA ISLAM DALAM PERSPEKTIF IMAM AL-GHAZĀLĪ - nadzirotul Masruroh (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2019)
Ethics is one part that can’t be given a distance from the discipline of philosophy. This happened because Greek philosophy also contributed to the birth of Islamic philosophy. In addition, ethics is also a very vital and substantial part of the discipline. Al-Ghazālī himself is a scholar, a philosopher, and a Sufi who is very intelligent and productive. In this case, the concept of Islamic ethics according to al-Ghazālī towards the opinions of philosophers who lead to disbelief, there are three problems, first, the natural faith. Second, God does not know things that are particular (juziyat), but only knows things that are universal (kulliyāt). Third, physical awakening. However, the ethical concept disputed by al-Ghazālī received a rebuttal from one of the Islamic leaders who were no less great, namely Ibn Rushd.